Pertumbuhan dan Hasil Kailan (Brassica oleraceae var. Albograba) pada Berbagai Jarak dan Media Tanam dengan Sistem Hidroponik - Putri, Faradilla Melia; Putri, Sekar Utami; Ali, Fahri; Rahhutami, Ratih; Khafidhan, Abied (Journal of Horticulture Production Technology, 2025)
This study aimed to evaluate the growth and yield response of kailan (Brassica oleraceae var. Albograba) to various plant spacings and growing media under a hydroponic NFT system. The experiment was conducted from September to November 2024 using a split-plot randomized block design with two factors: plant spacing (10 × 10 cm, 15 × 15 cm, and 20 × 20 cm) and growing media (cocopeat, rice husk charcoal, and rockwool), resulting in nine treatment combinations with three replications. Observed variables included plant height, number of leaves, leaf width, leaf length, fresh weight per plant, fresh weight per plot, and dry weight per plant. The results showed that plant spacing significantly affected plant height and fresh weight per plot, with the closest spacing (10 × 10 cm) yielding the highest biomass accumulation per plot. Growing media had a significant effect on all measured variables, where cocopeat consistently produced the highest values for plant height, leaf growth, fresh weight, and dry weight, followed by rice husk charcoal, while rockwool resulted in the lowest performance. No significant interaction was found between plant spacing and growing media. Overall, the study demonstrates that a spacing of 10 × 10 cm combined with cocopeat as the growing medium provides the most optimal growth and yield in hydroponic kailan cultivation.